The effect of the Rochagan on radiolabeling with (99m)Tc - Holanda, C. M. C. X.; Silva-Júnior, M. F.; Alves, R. C.; Barbosa, V. S. A.; Silva, R. P.; Rocha, L. G.; Medeiros, A. C. (Cellular and Molecular Biology, 2009)
Radionuclides are used in nuclear medicine by variety of diagnostic procedures. The labeling of red blood cells (RBC) with 99mTc is a current method applied in clinical nuclear medicine. Drugs can alter this labeling and modify the disposition of the radiopharmaceuticals. The influence of Rochagan on the labeling of blood constituents with 99mTc was reported. Samples of blood were incubated with different concentrations of Rochagan (0%; 6.25%; 12.5%; 25%; 50%; 100%). Stannous chloride and 99mTc (3.7MBq/mL) were added. Plasma (P) and (RBC) were isolated and precipitated with thricloroacetic acid 5%. The insoluble (IF) and soluble fractions (SF) were separated. The %ATI in RBC, IF-P and IF-RBC were calculated. The %ATI on RBC decreased significantly (p<0.05) from control to all concentrations of Rochagan, respectively: 90.15±0.14(control) to 70.80±4.21; to 64.36±0.33; to 57.30±1.56; to 50.28±2.71; to 42.41±2.24; on IF-RBC, respectively: 84.70±0.87(control) to 67.16±4.38; to 63.63±2.92; to 59.02±3.17; to 43.75±1.00; to 24.15±0.94 and also on IF-P, respectively: 83.46±1.09(control) to 50.90±3.36; to 35.46±4.13; to 35.78±2.31; to 28.74±3.09; to 19.66±1.34. The analyses were performed by T-Student and Mann Whitney tests, p<0.05. This effect was probably due to products present in Rochagan that may complex with ions or have a direct/indirect effect on intracellular stannous ion concentration.